Near-Infrared Confocal Reflectance Scanning Laser Ophthalmoscopy (SLO) and Short-Wavelength Autofluorescence Imaging in Cystic Diabetic Macular Edema - Fariba Ghassemi; Fatemeh Bazvand; Houshang Faghihi; Ramak Roohipourmoallai; Maryam Masoumi; Sepide Jamali; Masoumeh Mohebbi; Siamak Sabour (Journal of Ophthalmology)
Objective. To characterize results of short-wavelength autofluorescent (SW-AF) and near-infrared confocal reflectance scanning laser ophthalmoscopy (NIR-cR SLO) imaging in cystic diabetic macular edema (DME). Design. Cross-sectional study. Participants: 104 eyes from 52 naïve treatment patients with DME and mild to moderate nonproliferative diabetic retinopathy (NPDR) Methods: complete ocular examination, best-corrected visual acuity (BCVA), and imaging were performed. Results. In NIR-cR SLO, small/medium and large-sized cysts presented with decreased and increased reflectance, respectively. In SW-AF, increased and decreased autofluorescence, corresponding to medium-/large- and small-sized cysts were noted. Mainly, the lower NIR reflectance was associated with petaloid edema pattern in SW-AF (P=0.011), BCVA (logMAR) (P=0.056), subretinal fluid (P=0.035), and the involved layers of retina by cysts (P<0.001) in Pearson chi-square test. Fair agreement of 0.31 (P<0.001) between NIR-cR SLO and late FA leakage was found by the weighted kappa test. In regression analysis, NIR-cR SLO abnormality is highly correlated with outer and inner nuclear layers location of the cystic changes. Conclusions. The size of cysts and involved layers affect presenting features of SW-AF and NIR reflectance.